Congenitally Corrected Transposition of the Great Arteries in the Adult - Amaral,Fernando (2022)
ABSTRACT Introduction: Congenitally corrected transposition of the great arteries (CCTGA) is a rare anomaly. Current data available regarding adult cases is derived from small series, information simultaneously presented in pediatric publications, and one classical multicenter study. This review, not aimed to exhaust the subject, has the purpose to examine the literature addressing presentation, diagnostic methodology, and management of afflicted adult patients. Methods: A comprehensive search was undertaken in three major databases (PubMed, Cochrane, SciELO), using the keywords “congenitally corrected transposition of the great arteries” and “adults”. Relevant articles in English, Spanish, and Portuguese were extracted and critically appraised in this review. Steps for study selection were: (1) identification of titles of records through databases searching, (2) removal of duplicates, (3) screening and selection of abstracts, (4) final inclusion in the study. Results: Four hundred sixty-five publications on CCTGA in adult patients were retrieved, and 166 were excluded; 299 studies were used for this review including 76 full-text articles, 70 studies related to general aspects of the subject, and, due to the small number of publications, 153 case reports. Sixty-one articles referring to combined experiences in pediatric and adult patients and judged to be relevant, but retrieved from another sources, were also included. Conclusion: Albeit clinical presentation and diagnostic criteria have been well stablished, there seems to be room for discussion related to clinical and surgical management of CCTGA in adults. Considering the rarity of the disease, well designed multicenter studies may provide answers.